2006
DOI: 10.1007/s00264-006-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

De Quervain’s disease: efficacy of intra-sheath triamcinolone injection

Abstract: The methods and clinical outcomes of intrasheath triamcinolone injection in the treatment of de Quervain's disease are described. We used 38 hands of 36 patients. A mixture of 1 ml of triamcinolone and 1 ml of 1% lidocaine hydrochloride was injected, with an interval of 2 weeks. The fluid was injected into one point above the induration for the first 18 hands and into two points over the extensor pollicis brevis and abductor pollicis longus tendon in the induration for hands 19-38. The efficacy rate was 89%, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 14 publications
5
66
0
6
Order By: Relevance
“…Meanwhile, several authors published anatomical variations of the first extensor compartment. The accurate injection of triamcinolone into the sheath of both the extensor pollicis brevis and abductor pollicis longus tendon was considered very effective for DD in a recent study [13]. According to Zingas [17], the extensor pollicis brevis compartment was often missed in injections.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, several authors published anatomical variations of the first extensor compartment. The accurate injection of triamcinolone into the sheath of both the extensor pollicis brevis and abductor pollicis longus tendon was considered very effective for DD in a recent study [13]. According to Zingas [17], the extensor pollicis brevis compartment was often missed in injections.…”
Section: Discussionmentioning
confidence: 99%
“…15 Takuya Sawaizumi, 2007 claimed 94% success rate in their study in which they locally injected Triamcinolone for patients with De Quervain's disease. He concluded 90% of patients were fully satisfied, relapse was seen in 26% of patients, and complications were seen in 32% [16] . McDermott JD et al, reported in 2012 that at a follow up of 6 weeks, no complications were noted and 36 of the 37 wrist (97%).…”
Section: Discussionmentioning
confidence: 99%
“…These nonoperative modalities minimize repetitive loading of the first dorsal compartment Patient with de quervains tenosynovitis often complain of pain at the radial styloid, but this has to be differentiated from many other causes of pain like Wartenburg syndrome, cmc joint arthritis, C6 cervical radiculopathy, intersection syndrome, intercarpal instabilities, scaphoid fracture which all may produce a positive finkelsteins test 9 .The injection of steroid with local anaesthetic agent in the tendon sheath of the first dorsal compartment muscles is considered effective. 10 We recommend maximum of 2 trials of …”
Section: Discussionmentioning
confidence: 99%